Solid-liquid hybrid electrolyte membrane for lithium secondary batteries
Patent Information
- Application Number
- JP2024549201
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-10-25
- Filing Date
- 2023-10-20
- Publication Date
- 2025-03-13
AI Technical Summary
【0021】 本発明の一観点によるリチウム二次電池用固相-液相ハイブリッド電解質膜は、常圧及び圧力を印加した条件下でも液漏れ及び揮発が発生せず、イオン伝導度が高く、安定性及び機械的強度に優れている。
Smart Images

Figure 2025506738000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0138019 dated October 25, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a solid-liquid hybrid electrolyte membrane for a lithium secondary battery. [Background technology]
[0003] Lithium secondary batteries are becoming increasingly important due to the increasing use of automobiles, computers, and mobile devices. Among them, there is a particular demand for the development of lithium secondary batteries that are lightweight and have high energy density. Such lithium secondary batteries are composed of a separator between the positive and negative electrodes, and a liquid or solid electrolyte.
[0004] Lithium ion secondary batteries using liquid electrolytes have a structure in which a negative electrode and a positive electrode are separated by a separator, and therefore, if the separator is deformed or damaged by an external impact, a short circuit occurs, which can lead to leakage or volatilization of the electrolyte, or the risk of overheating or explosion. Therefore, there is a need to improve the safety of lithium ion secondary batteries using conventional liquid electrolytes.
[0005] In addition, all-solid-state batteries using solid electrolytes can increase the stability of the battery and prevent electrolyte leakage, improving the reliability of the battery. However, solid electrolytes have a problem in that the ion conductivity at room temperature is very low, which reduces the battery performance. Therefore, even if solid electrolytes are used, there is still a need to develop a solid electrolyte membrane that has high energy density and improved processability.
[0006] Therefore, there is a need to secure a technology for lithium ion secondary batteries that use a leak-free solid-liquid hybrid or solid electrolyte instead of the conventional liquid electrolyte for ion transport. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Korean Patent Publication No. 2003-0097009 Summary of the Invention [Problem to be solved by the invention]
[0008] An aspect of the present invention is to provide a solid-liquid hybrid electrolyte membrane for a lithium secondary battery, which does not leak or volatilize in normal and high pressure environments, has excellent mechanical strength, and has high ionic conductivity, and to provide a lithium secondary battery having improved performance including the same.
[0009] Other objects and advantages of the present invention will become apparent from the following description. Also, it is easily understood that the objects and advantages of the present invention can be realized by the means or methods recited in the claims and their combinations. [Means for solving the problem]
[0010] One aspect of the present invention provides a solid-liquid hybrid electrolyte membrane comprising: a liquid-phase polyhedral oligomeric silsesquioxane (POSS) represented by the following formula 1; a polymer including a functional group having compatibility with the POSS; and a lithium salt: [Chemical formula 1] [ka] In the above Chemical Formula 1, R are the same or different and are each independently selected from the group consisting of groups represented by the following chemical formulas 1-1 to 1-4: [Chemical formula 1-1] [ka] [Chemical formula 1-2] [ka] [Chemical formula 1-3] [ka] [Chemical formula 1-4] [ka] In the above Chemical Formulas 1-1 to 1-4, L1 to L5 are C1 to C30 alkylene groups, R1 to R4 are selected from the group consisting of hydrogen; a hydroxy group; an amino group; a thiol group; a C1 to C30 alkyl group; a C2 to C30 alkenyl group; a C2 to C30 alkynyl group; a C1 to C30 alkoxy group; and a C1 to C30 carboxy group; m and n are the same or different and each independently represents an integer of 0 to 10; * indicates the bond position.
[0011] In one embodiment of the present invention, in the above Chemical Formulas 1-1 to 1-4, L1 to L5 are a C1 to C10 alkylene group, R1 to R4 are hydrogen, a hydroxyl group, or a C1 to C30 alkyl group, and m and n are the same or different and each independently is an integer of 0 to 10.
[0012] In one embodiment of the present invention, in Chemical Formula 1, R is selected from the group consisting of a polyethylene glycol group, a glycidyl group, an octasilane group, and a methacryl group.
[0013] In one embodiment of the present invention, in the polymer having the functional group, the polymer may be one in which polypropylene carbonate (PPC), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN) or polyvinylpyrrolidone (PVP) is formed in the main chain or side chain.
[0014] In one embodiment of the invention, the functional group is selected from the group consisting of trifluoroethylene, tert-butyl acrylate, methyl methacrylate, styrene, vinyl pyridine, acrylic acid, chloride, vinyl acetate, vinyl imidazole, acrylamide, lactide, ethylene oxide, and butyl acrylate.
[0015] In one embodiment of the invention, the lithium salt comprises one or more selected from the group consisting of LiPF6, LiBF4, LiSbF6, LiAsF6, LiOH, LiOH·H2O, LiBOB, LiClO4, LiN(C2F5SO2)2, LiN(CF3SO2)2, CF3SO3Li, LiC(CF3SO2)3, LiC4BO8, LiTFSI, LiFSI, LiClO4, and combinations thereof.
[0016] In one embodiment of the present invention, the content ratio of the polymer containing a functional group compatible with the POSS and the polyhedral oligomeric silsesquioxane is 1:4 to 1:9.5.
[0017] In one embodiment of the present invention, the content ratio of the polyhedral oligomeric silsesquioxane and the lithium salt in the liquid phase is 10:1 to 1:5.
[0018] In one embodiment of the present invention, the ionic conductivity of the electrolyte membrane is 8.0×10 -7 ~2.0×10 -4 S / cm.
[0019] In one embodiment of the present invention, the electrolyte membrane has a thickness of 1 to 200 μm.
[0020] Another aspect of the present invention provides a lithium secondary battery comprising: a positive electrode; a negative electrode; and a solid-liquid hybrid electrolyte membrane according to the present invention. Effect of the Invention
[0021] The solid-liquid hybrid electrolyte membrane for a lithium secondary battery according to one aspect of the present invention does not leak or volatilize even under normal pressure or under pressure, has high ionic conductivity, and is excellent in stability and mechanical strength.
[0022] In addition, the lithium secondary battery including the solid-liquid hybrid electrolyte membrane for lithium secondary batteries has excellent charge / discharge characteristics and life characteristics. [Brief description of the drawings]
[0023] [Figure 1] FIG. 1 is a schematic diagram of a solid-liquid hybrid electrolyte membrane according to one aspect of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] The present invention will now be described in detail with reference to the accompanying drawings so that those skilled in the art can easily understand the present invention. However, the present invention may be embodied in various different forms and is not limited to the present specification.
[0025] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that is consistent with the technical idea of the present invention, based on the principle that the inventor can appropriately define the concept of the term in order to best describe his / her invention.
[0026] The terms used in this specification are merely used for the purpose of explanation and should not be interpreted as limiting. The singular expression includes the plural expression unless the context clearly indicates otherwise. In this specification, the terms "comprise" or "have" and the like specify the presence of the features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, and should be understood not to preclude the presence or addition of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.
[0027] The present invention relates to a solid-liquid hybrid electrolyte membrane, a method for producing the same, and a lithium secondary battery including the same.
[0028] A solid-liquid hybrid electrolyte membrane according to one aspect of the present invention includes a solid-phase polymer and a liquid-phase polyhedral oligomeric silsesquioxane (POSS). The solid-liquid hybrid electrolyte membrane includes a liquid phase and has a solid-phase shape, and does not leak or volatilize under normal pressure or pressure application conditions. The polymer may include a functional group having compatibility with the POSS. The polymer including the functional group may be in the form of a copolymer including the functional group or in the form of a polymer bonded to the functional group. The form of the polymer is not particularly limited as long as it has a structure including the functional group.
[0029] Such a solid-liquid hybrid electrolyte membrane contains a predetermined amount of liquid-phase polyhedral oligomeric silsesquioxane in a solid-phase polymer chain structure, and may be one in which the liquid-phase polyhedral oligomeric silsesquioxane is impregnated into the solid-phase polymer chain structure, or one in which the liquid-phase polyhedral oligomeric silsesquioxane is coated on the portion or surface of the solid-phase polymer that comes into contact with the solid-phase polymer.
[0030] The solid-liquid hybrid electrolyte membrane according to the present invention includes a solid-phase polymer having low ionic conductivity, and the functional group contained in the solid-phase polymer serves to improve the compatibility between the solid-phase polymer and the liquid-phase polyhedral oligomeric silsesquioxane, and the content of the liquid-phase polyhedral oligomeric silsesquioxane is increased, thereby ensuring improved ionic conductivity compared to conventional solid electrolyte membranes, and at the same time, having mechanical strength sufficient for free-standing.
[0031] 1 is a diagram showing a schematic structure of a solid-liquid hybrid electrolyte membrane according to one aspect of the present invention. The present invention will now be described in more detail with reference to the drawings.
[0032] 1, a solid-liquid hybrid electrolyte membrane (10) according to one aspect of the present invention comprises a solid-phase polymer (1) and a predetermined amount of a liquid-phase polyhedral oligomeric silsesquioxane (2). The solid-phase polymer (1) contains a functional group that is highly compatible with the liquid-phase polyhedral oligomeric silsesquioxane (2).
[0033] The solid-phase polymer (1) is a polymer substance that is solid at room temperature and has low solubility in an electrolyte solution.
[0034] The liquid phase polyhedral oligomeric silsesquioxane (2) is liquid at room temperature. When the liquid phase polyhedral oligomeric silsesquioxane is thermally cured, a polymerization reaction occurs and it can be changed into a solid. According to the present invention, a solid-liquid hybrid electrolyte membrane can be manufactured by mixing a solid phase polymer and a liquid phase polyhedral oligomeric silsesquioxane in a specific ratio. A more detailed description is given below.
[0035] The solid-liquid hybrid electrolyte membrane according to one aspect of the present invention may include a liquid-phase polyhedral oligomeric silsesquioxane (POSS) represented by the following formula 1: a polymer including a functional group having compatibility with the POSS; and a lithium salt: [Chemical formula 1] [ka] In the above Chemical Formula 1, According to another embodiment of the present invention, in the above-mentioned chemical formula 1, R are the same or different and each independently selected from the group consisting of groups represented by the following chemical formulae 1-1 to 1-4: [Chemical formula 1-1] [ka] [Chemical formula 1-2] [ka] [Chemical formula 1-3] [ka] [Chemical formula 1-4] [ka] In the above Chemical Formulas 1-1 to 1-4, L1 to L5 are C1 to C30 alkylene groups, R1 to R4 are selected from the group consisting of hydrogen; a hydroxy group; an amino group; a thiol group; a C1 to C30 alkyl group; a C2 to C30 alkenyl group; a C2 to C30 alkynyl group; a C1 to C30 alkoxy group; and a C1 to C30 carboxy group; m and n are the same or different and each independently represents an integer of 0 to 10; * indicates the bond position.
[0036] The polyhedral oligomeric silsesquioxane (POSS) has various structures such as a random structure, a ladder structure, a cage structure, and a partial cage structure. Among them, the polyhedral oligomeric silsesquioxane contained in the solid-liquid hybrid electrolyte membrane according to the present invention has a silica cage structure having a diameter of about 1 to 5 nm depending on the cage size, and is an organic-inorganic composite having properties of both inorganic silica (SiO2) and organic silicon (R2SiO). The polyhedral oligomeric silsesquioxane reduces the voids in the electrolyte, allowing it to form a more solid and dense structure, thereby improving mechanical properties and mechanical strength.
[0037] The present inventors have found that the ionic conductivity can be improved by mixing a solid-phase polymer having low ionic conductivity with a liquid-phase polyhedral oligomeric silsesquioxane represented by the following chemical formula 1. By mixing the solid-phase polymer of the present invention with a liquid-phase polyhedral oligomeric silsesquioxane, the polyhedral oligomeric silsesquioxane is positioned between the polymer chains, facilitating the movement of the polymer chains, and thus allowing the mobility of lithium ions to be easily achieved, thereby improving the ionic conductivity. In addition, since the solid-phase polymer contains a functional group that is compatible with the POSS, the content of POSS in the solid electrolyte can be further increased. The liquid-phase polyhedral oligomeric silsesquioxane represented by the following chemical formula 1 is as follows: [Chemical formula 1] [ka] In the above Chemical Formula 1, R are the same or different and are each independently selected from the group consisting of groups represented by the following chemical formulas 1-1 to 1-4: [Chemical formula 1-1] [ka] [Chemical formula 1-2] [ka] [Chemical formula 1-3] [ka] [Chemical formula 1-4] [ka] In the above Chemical Formulas 1-1 to 1-4, L1 to L5 are C1 to C30 alkylene groups, R1 to R4 are selected from the group consisting of hydrogen; a hydroxy group; an amino group; a thiol group; a C1 to C30 alkyl group; a C2 to C30 alkenyl group; a C2 to C30 alkynyl group; a C1 to C30 alkoxy group; and a C1 to C30 carboxy group; m and n are the same or different and each independently represents an integer of 0 to 10; * indicates the bond position.
[0038] In Formula 1, R may have one or more functional groups capable of binding with a lithium ion.
[0039] In one embodiment of the present invention, R may be a group represented by chemical formula 1-1, in which L1 and L2 may be C1 to C30 alkylene groups, preferably C1 to C20 alkylene groups, and more preferably C1 to C10 alkylene groups. In the above formula 1-1, R1 may be hydrogen, a C1-C30 alkyl group, a C2-C30 alkenyl group, a C2-C30 alkynyl group, a C1-C30 alkoxy group, or a C1-C30 carboxy group, preferably a C1-C20 alkyl group, a C2-C20 alkenyl group, a C2-C20 alkynyl group, a C1-C20 alkoxy group, or a C1-C20 carboxy group, and more preferably a C1-C10 alkyl group, a C2-C10 alkenyl group, a C2-C10 alkynyl group, a C1-C10 alkoxy group, or a C1-C10 carboxy group.
[0040] In another embodiment of the present invention, R may be a group represented by chemical formula 1-2. In the chemical formula 1-2, L3 and L4 may be an alkylene group having C1 to C30, preferably an alkylene group having C1 to C20, and more preferably an alkylene group having C1 to C10.
[0041] In another embodiment of the present invention, R may be a group represented by chemical formulas 1 to 3. In the chemical formulas 1 to 3, R2 to R4 may be the same or different and each independently represent hydrogen, a hydroxyl group, a C1 to C30 alkyl group, a C2 to C30 alkenyl group, a C2 to C30 alkynyl group, or a C1 to C30 alkoxy group, preferably hydrogen, a hydroxyl group, a C1 to C20 alkyl group, a C2 to C20 alkenyl group, a C2 to C20 alkynyl group, or a C1 to C20 alkoxy group, more preferably hydrogen, a hydroxyl group, a C1 to C10 alkyl group, a C2 to C10 alkenyl group, a C2 to C10 alkynyl group, or a C1 to C10 alkoxy group.
[0042] In another embodiment of the present invention, R may be a group represented by chemical formulas 1 to 4. In said chemical formulas 1 to 4, L5 may be a C1 to C30 alkylene group, preferably a C1 to C20 alkylene group, and more preferably a C1 to C10 alkylene group.
[0043] For example, in the above formula 1, R may be selected from the group consisting of a polyethylene glycol group, a glycidyl group, an octasilane group, and a methacryl group, and R is [ka] (wherein m is an integer from 1 to 9); [ka] , [ka] , [ka] (wherein * is a binding position), but is not limited thereto.
[0044] In one embodiment of the present invention, the solid-phase polymer containing a functional group having good compatibility with POSS may be a polymer that does not undergo phase separation when mixed with the liquid-phase polyhedral oligomeric silsesquioxane. The polymer may be a solid-phase polymer that is compatible with the liquid-phase polyhedral oligomeric silsesquioxane when mixed in an appropriate ratio, i.e., has compatibility properties with the liquid-phase POSS and is likely to coexist.
[0045] Specifically, the polymer has a main chain or a side chain of polypropylene carbonate (PPC), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN) or polyvinylpyrrolidone (PVP).
[0046] In addition, the functional group may be selected from the group consisting of trifluoroethylene, tert-butyl acrylate, methyl methacrylate, styrene, vinyl pyridine, acrylic acid, chloride, vinyl acetate, vinyl imidazole, acrylamide, lactide, ethylene oxide, and butyl acrylate. The functional group can further improve the compatibility between the polymer and the liquid-phase POSS, increase the content of the liquid-phase POSS, and ultimately improve the ionic conductivity and strength.
[0047] In one embodiment of the present invention, the solid-liquid hybrid electrolyte membrane comprising the polymer and the liquid-phase polyhedral oligomeric silsesquioxane represented by Chemical Formula 1 may further comprise a lithium salt.
[0048] The lithium salt acts as a source of lithium ions in the battery, enabling basic lithium secondary battery operation and facilitating the movement of lithium ions between the positive and negative electrodes. The lithium salt may be, but is not limited to, one selected from the group consisting of LiPF6, LiBF4, LiSbF6, LiAsF6, LiOH, LiOH·H2O, LiBOB, LiClO4, LiN(C2F5SO2)2, LiN(CF3SO2)2, CF3SO3Li, LiC(CF3SO2)3, LiC4BO8, LiTFSI, LiFSI, LiClO4, and combinations thereof.
[0049] The content of the lithium salt may be 10 to 50 wt%, preferably 15 to 45 wt%, more preferably 20 to 40 wt%, based on 100 wt% of the total electrolyte membrane. If the content is less than 10 wt%, the ion conductivity of the electrolyte membrane may be low, and if the content is more than 50 wt%, the lithium salt is not dissociated in the electrolyte membrane and exists in a crystalline state, so it cannot contribute to the ion conductivity, but rather plays a role in hindering the ion conductivity, which may reduce the ion conductivity, and the polymer content is relatively reduced, which may weaken the mechanical strength of the solid-liquid hybrid electrolyte membrane, so the content is appropriately adjusted within the above range.
[0050] The liquid phase polyhedral oligomeric silsesquioxane and lithium salt are contained in an amount of 80 wt% or more, 83 wt% or more, 85 wt% or more, 88 wt% or more, or 90 wt% or more based on the total weight of the electrolyte membrane, thereby further improving the ion conductivity. The upper limit of the content of the liquid phase polyhedral oligomeric silsesquioxane and lithium salt is not particularly limited, but may be, for example, 93 wt% or less, 94 wt% or less, or less than 95 wt%. If the upper limit is exceeded, phase separation may occur during mixing and / or after membrane formation, the mixture may exist as a liquid phase instead of a solid phase, or liquid leakage may occur.
[0051] In one embodiment of the present invention, the content ratio of the polymer containing a functional group compatible with the POSS and the liquid-phase polyhedral oligomeric silsesquioxane may be 1:4 to 1:9.5, or 1:6 to 1:9.5, or 1:8 to 1:9.5, or 1:8.5 to 9.5, or 1:9 to 1:9.5. Due to the functional group compatible with the POSS, even if the content of the liquid-phase polyhedral oligomeric silsesquioxane increases, phase separation does not occur, a solid-phase membrane can be formed, and ion conductivity can be improved.
[0052] In one embodiment of the present invention, the content ratio of the polyhedral oligomeric silsesquioxane and the lithium salt in the liquid phase may be 10:1 to 1:5, preferably 10:1 to 1:3, preferably 10:1 to 1:2, preferably 10:1 to 1:1, and more preferably 10:1 to 2:1. When the content ratio of the polyhedral oligomeric silsesquioxane and the lithium salt in the liquid phase is less than 10:1 to 1:5, the amount of lithium ions is small and the ionic conductivity is reduced, and when the content ratio exceeds 10:1 to 1:5, the lithium ions are excessive and do not dissociate, causing precipitation or increasing the viscosity, resulting in a reduction in the ionic conductivity.
[0053] In one embodiment of the present invention, the ionic conductivity of the solid-liquid hybrid electrolyte membrane is 8.0×10 -7 ~2.0×10 -4 It may be S / cm.
[0054] In one embodiment of the present invention, the electrical resistance of the solid-liquid hybrid electrolyte membrane may be 10.0 to 60,000 ohms (Ω), and preferably 50.0 to 55,000 ohms (Ω).
[0055] In the solid-liquid hybrid electrolyte membrane, as the content of the liquid phase polyhedral oligomeric silsesquioxane relative to the polymer decreases, the electrical resistance of the electrolyte membrane may increase and the ionic conductivity of the electrolyte membrane may increase.
[0056] In one embodiment of the present invention, the thickness of the solid-liquid hybrid electrolyte membrane may be 1 to 200 μm, and preferably 5 to 195 μm. If the thickness of the solid-liquid hybrid electrolyte membrane is less than 1 μm, the mechanical strength of the electrolyte membrane is weak, which may cause difficulties in assembling a battery or cause an electrical short circuit. If the thickness of the solid-liquid hybrid electrolyte membrane is more than 200 μm, the energy density is low and the ion conductivity is low, making it difficult to apply the membrane to a battery.
[0057] In one embodiment of the present invention, there is provided a lithium secondary battery comprising a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, wherein the separator may comprise the solid-liquid hybrid electrolyte membrane according to the present invention.
[0058] The positive electrode and the negative electrode each include a current collector and an electrode active material layer formed on at least one surface of the current collector, the active material layer including a plurality of electrode active material particles and a solid electrolyte. The electrodes may further include at least one of a conductive material and a binder resin, as necessary. The electrodes may further include various additives for the purpose of complementing or improving the physicochemical properties of the electrodes.
[0059] In the present invention, the negative electrode active material may be any material that can be used as a negative electrode active material for a lithium ion secondary battery. For example, the negative electrode active material may be carbon such as non-graphitizable carbon or graphite-based carbon; Li x Fe2O3(0≦x≦1), Li x WO2(0≦x≦1), Sn x Me 1-x Me' y O z(Me is Mn, Fe, Pb, and Ge, Me' is Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, and halogens, 0 < x ≤ 1; 1 ≤ y ≤ 3; 1 ≤ z ≤ 8), etc. metal composite oxides; lithium metal; lithium alloys; silicon-based alloys; tin-based alloys; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxides; lithium titanium oxides, etc. One or more selected therefrom may be used. In a specific embodiment, the negative electrode active material may contain a carbon-based material and / or Si.)
[0060] In the case of the positive electrode, the electrode active material may be used without limitation as long as it can be used as the positive electrode active material of a lithium ion secondary battery. For example, the positive electrode active material is a layered compound such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; chemical formula Li 1+x Mn 2-x O4 (where x is 0 to 0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5, Cu2V2O7; chemical formula LiNi 1-x M x O2 (where M = Co, Mn, Al, Cu, Fe, Mg, B, or Ga, and x = 0.01 to 0.3), Ni-site type lithium nickel oxide represented by; chemical formula LiMn 2-x M x O2 (where M = Co, Ni, Fe, Cr, Zn, or Ta, and x = 0.01 to 0.1) or lithium manganese composite oxide represented by Li2Mn3MO8 (where M = Fe, Co, Ni, Cu, or Zn); LiNi x Mn 2-xExamples of the lithium manganese oxide include, but are not limited to, lithium manganese oxide having a spinel structure represented by O4, LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion, disulfide compounds, and Fe2(MoO4)3.
[0061] In the present invention, the current collector is an electrically conductive material such as a metal plate, and an appropriate one may be used according to the polarity of the current collector electrode as is known in the field of secondary batteries.
[0062] In the present invention, the conductive material is for imparting electrical conductivity to the electrode, and is usually added in an amount of 1 to 30% by weight based on the total weight of the mixture including the electrode active material. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has electrical conductivity, and may include, for example, one or a mixture of two or more conductive materials selected from graphite such as natural graphite or artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, and other carbon-based materials; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and polyphenylene derivatives.
[0063] In the present invention, the binder resin plays a role of making the negative electrode active material particles adhere well to each other and to the current collector, and is not particularly limited as long as it is a component that assists in binding the active material to the conductive material and the current collector, and examples thereof include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber, fluororubber, various copolymers, etc. The binder resin may be generally contained in a range of 1 to 30% by weight, or 1 to 10% by weight, based on 100% by weight of the electrode layer.
[0064] Meanwhile, in the present invention, the electrode active material layer may contain one or more additives such as an oxidation stabilizing additive, a reduction stabilizing additive, a flame retardant, a heat stabilizer, and an antifogging agent, if necessary.
[0065] The present invention will be described in more detail below with reference to examples. However, the following examples are for illustrating the present invention, and the scope of the present invention is not limited to these examples.
[0066] Working Example [Example 1] Solution A was prepared by adding 10 wt% polyvinylidene fluoride (PVDF) (PVP-PVDF, Polymersources) containing poly(vinyl pyridine, PVP) as a polymer to N-methyl-2-pyrrolidone (NMP) and thoroughly stirring at 60°C.
[0067] Solution B was prepared by thoroughly stirring polyethylene glycol-polyhedral oligomeric silsesquioxane (PEG-POSS) (Hybridplastics) and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) (Sigma-Aldrich) in a weight ratio of 10:4 at 60°C.
[0068] The A and B solutions were thoroughly stirred at room temperature for 24 hours so that the content ratio of PVP-PVDF:PEG-POSS-LiTFSI became 15:85.
[0069] The prepared solution was coated on a stainless steel foil using a doctor blade, and then vacuum dried at 100° C. for 12 hours to prepare a solid electrolyte membrane.
[0070] [Example 2] A solid electrolyte membrane was prepared in the same manner as in Example 1, except that the content ratio of PVP-PVDF:PEG-POSS-LiTFSI was 10:90.
[0071] [Example 3] A solid electrolyte membrane was prepared in the same manner as in Example 1, except that the content ratio of PVP-PVDF:PEG-POSS-LiTFSI was 7:93.
[0072] [Example 4] A solid electrolyte membrane was prepared in the same manner as in Example 1, except that polyvinyl pyrrolidone (PVP) containing polyvinyl acetate (PVAc) (PVAc-PVP, polyvinyl pyrrolidone-co-vinyl acetate, Polymer source) was used instead of polyvinyl pyridine-containing polyvinylidene fluoride (PVP-PVDF) as the polymer.
[0073] [Comparative Example 1] A solid electrolyte membrane was prepared in the same manner as in Example 1, except that a polymer having no functional group (PVDF (Sigma-Aldrich)) was used and the content ratio of PVDF:PEG-POSS-LiTFSI was 20:80.
[0074] [Comparative Example 2] A solid electrolyte membrane was prepared in the same manner as in Example 1, except that PVDF without functional groups was used as the polymer and the content ratio of PVDF:PEG-POSS-LiTFSI was 15:85.
[0075] [Comparative Example 3] A solid electrolyte membrane was prepared in the same manner as in Example 1, except that the content ratio of PVP-PVDF:PEG-POSS-LiTFSI was 5:95.
[0076] [Comparative Example 4] A solid electrolyte membrane was prepared in the same manner as in Example 1, except that the content ratio of PVP-PVDF:PEG-POSS-LiTFSI was 20:80.
[0077] [Comparative Example 5] A solid electrolyte membrane was prepared in the same manner as in Example 1, except that polyvinylpyrrolidone (PVP, polyvinyl pyrrolidone, Polymersource) was used instead of polyvinylpyridine-containing polyvinylidene fluoride (PVP-PVDF) and the content ratio of PVP:PEG-POSS-LiTFSI was 33:67.
[0078] [Comparative Example 6] A solid electrolyte membrane was prepared in the same manner as in Example 1, except that polyvinylpyrrolidone (PVP, polyvinyl pyrrolidone, Polymersource) was used instead of polyvinylpyridine-containing polyvinylidene fluoride (PVP-PVDF) and the content ratio of PVP:PEG-POSS-LiTFSI was 15:85.
[0079] Experimental Example 1: Ionic conductivity of solid-liquid hybrid electrolyte membrane at normal pressure Using an analyzer VMP3 (Bio logic science instrument), electrochemical impedance was measured at 23° C. with an amplitude of 10 mV and a scan range of 500 KHz to 20 MHz, and based on this, ionic conductivity was calculated using the following formula 1.
[0080] [Formula 1]
number
[0081] The ionic conductivity calculated using the above formula 1 is shown in Table 1 below.
[0082] [Table 1]
[0083] As a result, as shown in Table 1, it was confirmed that an electrolyte membrane containing a polymer having a functional group compatible with POSS and POSS in a specific content ratio was formed in a solid-phase membrane and had improved ionic conductivity.
[0084] In Comparative Examples 2 and 6, the POSS content was increased by using PVDF and PVP, which do not contain functional groups compatible with POSS, as polymers. Since PVP does not contain functional groups compatible with POSS, it can be seen that phase separation occurred. [Explanation of symbols]
[0085] 1: Solid-liquid hybrid electrolyte membrane 10: Polymers in the solid phase 20: Liquid-phase polyhedral oligomeric silsesquioxane
Claims
1. A solid-liquid hybrid electrolyte membrane comprising: a liquid-phase polyhedral oligomeric silsesquioxane (POSS) represented by the following formula 1; a polymer having a functional group compatible with the POSS; and a lithium salt: [Chemical formula 1] 【Chemistry 1】 In the above Chemical Formula 1, R are the same or different, and each independently is selected from the group consisting of groups represented by the following chemical formulas 1-1 to 1-4: [Chemical formula 1-1] 【Chemistry 2】 [Chemical formula 1-2] 【Chemistry 3】 [Chemical formula 1-3] 【Chemistry 4】 [Chemical formula 1-4] 【Chemistry 5】 In the above Chemical Formulas 1-1 to 1-4, L1 to L5 are C1 to C30 alkylene groups, R1 to R4 are selected from the group consisting of hydrogen; a hydroxy group; an amino group; a thiol group; a C1 to C30 alkyl group; a C2 to C30 alkenyl group; a C2 to C30 alkynyl group; a C1 to C30 alkoxy group; and a C1 to C30 carboxy group; m and n are the same or different and each independently represents an integer from 0 to 10; * indicates the bond position.
2. In the above Chemical Formulas 1-1 to 1-4, L1 to L5 are C1 to C10 alkylene groups, R1 to R4 are hydrogen; a hydroxy group; or a C1 to C30 alkyl group; 2. The solid-liquid hybrid electrolyte membrane according to claim 1, wherein m and n are the same or different and each independently represents an integer of 0 to 10.
3. 2. The solid-liquid hybrid electrolyte membrane according to claim 1, wherein in Chemical Formula 1, R is selected from the group consisting of a polyethylene glycol group, a glycidyl group, an octasilane group, and a methacryl group.
4. In the polymer having a functional group, 2. The solid-liquid hybrid electrolyte membrane according to claim 1, wherein the polymer has a main chain or a side chain of polypropylene carbonate (PPC), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), or polyvinylpyrrolidone (PVP).
5. The functional groups compatible with POSS are trifluoroethylene, tert-butyl acrylate, methyl methacrylate, styrene, vinyl pyridine, acrylic acid, chloride, vinyl acetate, vinyl imidazole, acrylamide, lactide, ethylene oxide, and butyl acrylate.
2. The solid-liquid hybrid electrolyte membrane according to claim 1, wherein the electrolyte is selected from the group consisting of:
6. The lithium salt is LiPF 6 , LiBF 4 , LiSbF 6 , LiAsF 6 , LiOH, LiOH・H 2 O, LiBOB, LiClO 4 , LiN (C 2 F 5 SO 2 ) 2 , LiN(CF 3 SO 2 ) 2 , C.F. 3 SO 3 Li, LiC(CF 3 SO 2 ) 3 , LiC 4 B.O. 8 , LiTFSI, LiFSI, LiClO 4 2. The solid-liquid hybrid electrolyte membrane according to claim 1, comprising one or more selected from the group consisting of:
7. 2. The solid-liquid hybrid electrolyte membrane according to claim 1, wherein the content ratio of the polymer containing a functional group compatible with POSS and the polyhedral oligomeric silsesquioxane is 1:4 to 1:9.
5.
8. 2. The solid-liquid hybrid electrolyte membrane according to claim 1, wherein the content ratio of the polyhedral oligomeric silsesquioxane and the lithium salt in the liquid phase is 10:1 to 1:
5.
9. The ionic conductivity of the electrolyte membrane is 8.0×10 based on 25° C. -7 ~2.0 x 10 -4 2. The solid-liquid hybrid electrolyte membrane according to claim 1, wherein the electrochemical conductivity is 1.0 S / cm.
10. 2. The solid-liquid hybrid electrolyte membrane according to claim 1, wherein the electrolyte membrane has a thickness of 1 to 200 μm.
11. Positive electrode; A negative electrode; and A lithium secondary battery comprising the solid-liquid hybrid electrolyte membrane according to any one of claims 1 to 10.
Citation Information
Patent Citations
Electrolyte, method of preparing the same, and lithium secondary battery comprising the same
JP2016062895A
Enhanced ion conductivity of organic-inorganic polymer electrolyte nano-composites and dye-sensitized solar cell including the same
KR1020120109173A
Solid polymer electrolyte composition and lithium secondary battery including the same
US20150244025A1
Hybrid Electrolytes with Controlled Network Structures for Lithium Metal Batteries
US20180226679A1
KR2003-0097009